2004
DOI: 10.1017/s0790966700008296
|View full text |Cite
|
Sign up to set email alerts
|

The outcome of treatment in hostels

Abstract: Objectives: This paper aimed to examine the outcome of hostel treatment including the effect on hospitalisation rates.Methods: The work of the four medium/long term Gloucester hostels developed between 1983 and 1993, to provide 24-hour nursed care to ‘new long stay’ patients in Gloucester is described.Results: Fifty-eight patients with predominately severe mental illness were admitted to the hostels up to 1999, and demographic/illness data is presented. Mean duration of hostel stay was 4.8 years, and one third… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…Importantly, patients were also more satisfied with their living arrangement in the community when compared to hospital (61,67). Following their initial discharge to the community, a substantial proportion of patients subsequently moved to more independent settings with less than 24-hour staff supervision (60,(68)(69)(70). However, conversely, Chopra et al's small study of 18 people reported patients were less satisfied with their accommodation following the subsequent move, and were often still living in "restrictive" settings and unhappy about making recurrent moves (67).…”
Section: Studies Of Deinstitutionalization Programmesmentioning
confidence: 99%
“…Importantly, patients were also more satisfied with their living arrangement in the community when compared to hospital (61,67). Following their initial discharge to the community, a substantial proportion of patients subsequently moved to more independent settings with less than 24-hour staff supervision (60,(68)(69)(70). However, conversely, Chopra et al's small study of 18 people reported patients were less satisfied with their accommodation following the subsequent move, and were often still living in "restrictive" settings and unhappy about making recurrent moves (67).…”
Section: Studies Of Deinstitutionalization Programmesmentioning
confidence: 99%